2012
DOI: 10.1192/bjp.bp.111.105833
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to treatment guidelines in clinical practice: study of antipsychotic treatment prior to clozapine initiation

Abstract: Substantial delays to clozapine initiation remain and antipsychotic polypharmacy and high doses are commonly used prior to clozapine, despite treatment guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
260
5
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(289 citation statements)
references
References 25 publications
8
260
5
5
Order By: Relevance
“…In certain cases of non-response to clozapine, the use of other second-generation antipsychotics, augmentation strategies with antidepressants and/or mood stabilizers, combination of antipsychotics and electroconvulsive therapy have been suggested as treatment alternatives, however, with limited evidence for their efficacy [2,[21][22][23]. Despite this, it was reported that clinicians do often try other approaches before clozapine prescription and there could be long delays before prescription of clozapine [24,25].…”
Section: Discussionmentioning
confidence: 98%
“…In certain cases of non-response to clozapine, the use of other second-generation antipsychotics, augmentation strategies with antidepressants and/or mood stabilizers, combination of antipsychotics and electroconvulsive therapy have been suggested as treatment alternatives, however, with limited evidence for their efficacy [2,[21][22][23]. Despite this, it was reported that clinicians do often try other approaches before clozapine prescription and there could be long delays before prescription of clozapine [24,25].…”
Section: Discussionmentioning
confidence: 98%
“…No que se refere à terapêutica, os pacientes com ER, por não responderem a doses usuais das drogas antipsicóticas de primeira e de segunda geração, são geralmente tratados tanto com doses mais altas de medicação do que as habitualmente utilizadas como com polifarmácia 4 , o que pode explicar a significância estatística quanto ao número de antipsicóticos utilizados nesses pacientes 14,15 , em concordância, portanto, com os dados encontrados no presente estudo. Além disso, os pacientes não refratários utilizaram maior número de associações com antidepressivos e benzodiazepínicos, o que possivelmente pode ter ocorrido por causa da maior possibilidade do diagnóstico de comorbidades psiquiátricas em pacientes com esquizofrenia quando há controle adequado dos sintomas psicóticos 16 .…”
Section: Discussionunclassified
“…During phase 3 of the CATIE study, 51% of patients had previously discontinued medications due to ineffective therapeutic response, but only 11% of patients were offered clozapine during phase 3. Studies of clozapine utilization have shown that adherence to guidelines has been poor through the years with clozapine been consistently underutilized in the US, UK, Canada, New Zealand and Australia [9,[21][22][23][24][25][26][42][43][44][45][46]. In a study of the Veterans Health Administration, only 2% of patients affected by schizophrenia were receiving clozapine [22].…”
Section: Clozapine Prescribing Trendsmentioning
confidence: 99%
“…However, none of the newer SGAs could demonstrate superiority to clozapine and in the last decade many published clinical practice guidelines [13][14][15][16][17][18][19][20] have recommended that clozapine be prescribed to patients with treatment-resistant schizophrenia, which has been defined as not responsive to two trials of any other antipsychotic medication (either FGA or SGA). Despite such recommendations and the overwhelming evidence of clozapine effectiveness, prescribing of clozapine appears to be low, delayed and often preceded by attempts at polypharmacy treatment, which lacks clinical evidence of effectiveness [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%